Ethnobiology and Indigenous Knowledge about Medicinal Animals and Plants in the Balami Ethnic Group in Nepal - Timilsina, S.H.; Singh, N.B. (Journal of Institute of Science and Technology, 2015)
The main purpose of the study was to document the medicinal animals and plants used by the unique ethnic group; ‘Balami’, native of Okharpauwa VDC of Nuwakot district. The information was collected in the area using an integrated approach of zoological and botanical collections, group discussions, interviews and questionnaires. It enumerates an account of ethnography with the list of 65 animal species belonging to 31 orders, 46 families and 62 genera. Out of which 55 species are wild and 10 species are domesticated. The Balami utilize these animals mainly for food, medicine, companion, ceremony, agriculture etc. They use 15 species of animals for medicinal purpose among which 13 are wild and 2 are domesticated to cure 16 different types of diseases. Balami have brought altogether 185 different plant species into use. Among them 80 species are brought from the local forest, 87 species are cultivated and 18 species of the plants are purchased from the nearest market. These plant species are included under 65 families and 151 genera. They use 45 different plant species to cure 55 different diseases out of which 32 are wild, 12 are cultivated and 1 is purchased from the remote area. The present inventory will play a catalytic role for implementation of development programs in the region, recommendations of the conservation and sustainable use based on indigenous knowledge from the elder to the younger generations. Journal of Institute of Science and Technology, 2014, 19(2): 79-85